Білкові фракції препаратів желатину - Чурсіна, Ольга Олексіївна; Гержикова, Вікторія Григорівна; Зінкевич, Е. Л.; Бабич, Ірина Михайлівна (My University, 2007)
Наведено результати електрофоретичного дослідження білкових фракцій різних препаратів желатину, казеїну, яєчного альбуміну і рибного клею. Встановлено, що препарати желатину, які випускають у рідкому виді, відрізняються більш високим ступенем гідролізу і вмістом тільки низькомолекулярних білків з молекулярною масою 10000-17000 Да. У складі повітряно-сухих препаратів переважають високомолекулярні білки, поряд з якими присутні фракції низько- і середньомолекулярних білків. Аналогічний розподіл білків по молекулярних масах характерний також для казеїну, рибного клею і яєчного альбуміну. The results of electrophoresis evaluation of protein fractions of different preparations (gelatin, egg albumin etc) have been presented. It has been shown that liquid gelatin preparations are more responsible to hydrolyze and contain mostly low weight proteins with molecular weight from 10000 to 17000. Although high weight proteins are dominated in dry protein preparations, there are also medium and low weight fractions as well. The same proportions of protein fractions in egg albumin and fish glue is normal. A method for treatment of wine materials with liquid gelatin preparations has been tested under industrial conditions. Principal criteria which characterize properties of liquid gelatin preparations have been determined: color, odor, taste, the proportion (by weight) of dry matter, the proportion (by weight) of ash, the dynamic viscosity, pH, the protein fraction molecular weight, the tannin-precipitating ability, the ability to bind of pyrogallic hydroxyl groups and the proportion (by weight) of proline.
Keywords: желатин; танін; колоїдні помутніння; фенольні речовини; столові виноматеріали; gelatin; tannin; colloidal haze; phenolic substances; table wine materials; кафедра біотехнології продуктів бродіння і виноробства